AB0357 Does the Body Mass Index (BMI) Influence the Clinical Assessment of Synovitis in Rheumatoid Arthritis?. (9th June 2015) - Goossens, J.; Ottaviani, S.; Coustet, B.; Palazzo, E.; Dieudé, P.
Abstract : Background: It was suggested that obesity and adipose tissue could play a role in the course of rheumatoid arthritis (RA). Obesity, defined by a BMI ≥30 kg/m 2, is associated in some studies with increased risk of RA and might have a protective effect early during the disease. Obesity could also be associated with more severe functional and pain outcomes. Regarding this excess adipose tissue and more pain score in obese patient, it could be speculated that clinical assessment of swollen joint count and RA disease activity measurement might be affected by obesity. Objectives: The aim of the study was to assess the influence of BMI on clinical RA disease activity assessment by clinical exam in comparison with ultrasound (US). Methods: A total of 76 RA patients, fulfilled the ACR/EULAR criteria for RA, were included in this single-center transversal study. The following data were collected: BMI; gender; age; disease duration; disease activity score in 28 joints (DAS28); pain on a visual analog scale (VAS, 0-100 mm); tender joint count (TJC) and swollen joint count (SJC) in 28 sites; anti-CCP antibodies and rheumatoid factor (RF) status; erosive status; use of disease-modifying anti-rheumatic drugs (DMARDs), corticosteroids or previous biologic agents; erythrocyte sedimentation rate (ESR); and C-reactive protein (CRP) level. BMI was calculated as weight in kilograms divided by height in square meters. According to the World Health Organization criteria, normal BMI was defined as <25 kg/m 2, overweight 25-30 kg/m 2, and obesity ≥30 kg/m 2 . US assessment was performed the same day by one rheumatologist blinded to clinical data. An US SJC on 28 sites was measured for each patient. US synovitis was defined as a grey scale score ≥2 and/or Power Doppler ≥1. The primary outcome measure was the delta synovitis between clinical SJC and US SJC. Secondary outcomes were the delta DAS28 and the proportion of patient in Eular remission. Results: The distribution of patients with normal weight, overweight and obesity was 29 (38.2%), 33 (43.4%)and 14 (18.4%), respectively. The mean age was 53.8±11.8 years (51 (77%) of female). The mean disease duration was 12.3±9.2 years. Baseline characteristics did not differ between the three subgroups of BMI. In absolute values, the mean delta synovitis counts between US and clinical exam were not statistically different among normal weight (2.1), overweight (2.2) and obese patients (2.2). The delta (US – clinical exam) DAS28 was not modified in obese patients in comparison with other BMI subgroups. Finally, using US synovitis joint count in comparison with clinical exam assessment, did not affect the proportion of patients in Eular remission. Conclusions: BMI and particularly obesity do not influence the swollen joint count and disease activity measurement. Disclosure of Interest: None declared